Predicting horizontal impact sound transmission for complex floor systems: Using EN 12354-2:2000, finite element method, statistical energy analysis and analytical techniques. Issue 1 (March 2017) - Park, Aaron; Finley, Richard; Cater, John
Modifications to the New Zealand Building Code are currently being considered, which may create a requirement to assess impact noise horizontally not just vertically. The test would be similar to vertical tests as described in ISO 140-7:1998, but sound pressure levels are proposed to be measured instead in the closest living space in an adjacent apartment which shares a common floor system. This work seeks to identify and validate different mathematical and computational methods for predicting the results of horizontal impact tests. Three methodologies were tested: finite element method software, statistical energy analysis and an analytical solution derived from the governing partial differential equations. These methods were applied to two different floor systems: a concrete double tee floor and a concrete floor supported by concrete beams and columns. Limitations were found for all of the methods, and caution is advised when using these to design to horizontal impact noise criteria.